2015
DOI: 10.1155/2015/605946
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Vascular Endothelial Growth Factor Receptor 1 Prevents Inflammation and Vascular Leakage in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is a leading cause of blindness in working age adults. The objective of this study is to investigate the effects of vascular endothelial growth factor receptor 1 (VEGFR1) blockade on the complications of DR. Experimental models of diabetes were induced with streptozotocin (STZ) treatment or Insulin2 gene mutation (Akita) in mice. Protein expression and localization were examined by western blots (WB) and immunofluorescence (IF). mRNA expression was quantified by PCR array and real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 37 publications
(43 reference statements)
2
25
0
Order By: Relevance
“…In diabetic mice receiving control, VE-cadherin was found to be discontinuous or diffuse at the junctions of deep retinal capillaries (Fig. 3g) compared with non-diabetic animals, consistent with previous reports [5,18]. In contrast, CD5-2-treated diabetic mice displayed continuous VEcadherin expression at the junctions of microvessels in the deep plexus, with the level of VE-cadherin expression similar to that seen in non-diabetic animals (Fig.…”
Section: Cd5-2 Increases Ve-cadherin Expressionsupporting
confidence: 90%
See 1 more Smart Citation
“…In diabetic mice receiving control, VE-cadherin was found to be discontinuous or diffuse at the junctions of deep retinal capillaries (Fig. 3g) compared with non-diabetic animals, consistent with previous reports [5,18]. In contrast, CD5-2-treated diabetic mice displayed continuous VEcadherin expression at the junctions of microvessels in the deep plexus, with the level of VE-cadherin expression similar to that seen in non-diabetic animals (Fig.…”
Section: Cd5-2 Increases Ve-cadherin Expressionsupporting
confidence: 90%
“…A marked reduction in levels of VE-cadherin is seen in human retina obtained post-mortem from individuals with diabetes [15], while increased plasma levels have been observed in individuals with type 2 diabetes, suggesting that it is shed from the endothelium [16]. Higher levels of phosphorylation and degradation of VE-cadherin have been observed with increased vascular leakage in diabetic rodents [5,17,18]. Thus, a drug that restores the levels of VE-cadherin may have profound effects on the pathology of diabetic retinopathy, limiting vascular leakage and inhibiting angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the blockade of VEGFR1 suppressed vascular leakage and disorganization of ZO-1 (He et al, 2015). As we found the regulatory role of miR-15a/16 on the levels of TGF-beta3, VEGF, and tight junction proteins, we examined the effects of miR-15a/16 on the permeability of endothelial cells in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that TGF-beta signaling mediated an increase in VEGF in ARPE-19 cells under hyperglycemic conditions (Grigsby, Betts, Vidro-Kotchan, Culbert, & Tsin, 2012). Increased levels of VEGF signaling have also been shown in diabetic retina (Witmer et al, 2002) and the blockade of VEGFR1 suppressed retinal leukostasis, vascular leakage, and disorganization of zonula occludens-1 (ZO-1) (He et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…24,[56][57][58] In this study, the mouse STZ model was selected, since this is the most common diabetic mouse model described in literature. 24 Different research groups have used this model to assess vascular leakage, 43,[59][60][61][62] and although several studies indeed delineated leakage in the diabetic mouse retina, the Müller glia reactivity was also studied via histologic staining for vimentin retinal staining and showed significantly more IPL/INL crossing fibers during early (1.7-fold increase) and during midterm diabetes (2.7-fold increase). (F) Gliosis was also diminished with 61% and 48% for aflibercept and TAAC, respectively.…”
Section: Discussionmentioning
confidence: 99%